Indonesian EFL Students' attitude toward Oral Presentations - Riza Amelia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The present study aims at investigating Indonesian EFL students’s attitude toward oral-presentations in the local context. The design of the study was qualitative descriptive research. The participants were twenty-one English major students in semester 5. The data collection technique was open-ended questionaires. Data analysis was conducted by content analysis. The findings revealed that the EFL students’ view toward oral presentations were twofold, on one side they found it challenging, however, on the other side, they also found it useful to develop their skills. The challenges were some psychological issues and insufficient presentation skills during oral presentations. The benefits were that the EFL students thought that their L2 and academic skills were gradually improved through oral presentations. Furthermore, the findings recommend that future researchers may address how to solve the the problems and how to maximize the opportunities that were offered by oral presentations. Keywords: oral presentations, learner-centered approach, speaking skills.